Venetoclax resistance induced by activated T cells can be counteracted by sphingosine kinase inhibitors in chronic lymphocytic leukemia - Sarapura Martinez, Valeria J.; Buonincontro, Brenda; Cassarino, Chiara; Bernatowiez, Juliana; Colado, Ana; Cordini, Gregorio; Custidiano, Maria del Rosario; Mahuad, Carolina; Pavlovsky, Miguel A.; Bezares, Raimundo F.; Favale, Nicolás O.; Vermeulen, Mónica; et al. (Frontiers in Oncology, 2023)
The treatment of chronic lymphocytic leukemia (CLL) patients with venetoclax-based regimens has demonstrated efficacy and a safety profile, but the emergence of resistant cells and disease progression is a current complication. Therapeutic target of sphingosine kinases (SPHK) 1 and 2 has opened new opportunities in the treatment combinations of cancer patients. We previously reported that the dual SPHK1/2 inhibitor, SKI-II enhanced the in vitro cell death triggered by fludarabine, bendamustine or ibrutinib and reduced the activation and proliferation of chronic lymphocytic leukemia (CLL) cells. Since we previously showed that autologous activated T cells from CLL patients favor the activation of CLL cells and the generation of venetoclax resistance due to the upregulation of BCL-XL and MCL-1, we here aim to determine whether SPHK inhibitors affect this process. To this aim we employed the dual SPHK1/2 inhibitor SKI-II and opaganib, a SPHK2 inhibitor that is being studied in clinical trials. We found that SPHK inhibitors reduce the activation of CLL cells and the generation of venetoclax resistance induced by activated T cells mainly due to a reduced upregulation of BCL-XL. We also found that SPHK2 expression was enhanced in CLL cells by activated T cells of the same patient and the presence of venetoclax selects resistant cells with high levels of SPHK2. Of note, SPHK inhibitors were able to re-sensitize already resistant CLL cells to a second venetoclax treatment. Our results highlight the therapeutic potential of SPHK inhibitors in combination with venetoclax as a promising treatment option for the patients.